Pengaruh Penggunaan Video dan Pemberian Tugas terhadap Penguasaan Materi (Studi Perbandingan Penguasaan Materi menggunakan Video dan Metode konvensional) - juanda simanjuntak (Jurnal Euangelion, 2021)
The creativity of a teacher is required for achievement the mastery of material by students so that learning goal can be reached. The purpose of this research was to prove the effect of giving videos and assignments on mastery sunday school subject matter. This research uses quantitative research methods with a quasi experimental research design. Statistical data processing used SPSS version 22 software. The population of Sunday School research was group III of the students (Sunday School) of HKBP Simorangkir Resort Simorangkir, totally 46 pupils. The students were divided in two classes, the experimental class by 23 students, and control class by 23 students. The experimental class was given a treatment by giving videos and assignment methods, while in the control class only by convidential method without videos and assignments, but both of them were given pretest and posttest. The results of data analysis concluded that 1) there was a positive and significant influence between the use of video and mastery of subject amount 0.766; 2) There is a positive and significant influence between assignment to mastery the subject amount 0.847; 3) There is a positive and significant influence between the use of videos and assignments in subjects mastery amount 0.779 and 0.795. This study generally concludes that the use of video and assignments has an effect in improving the ability of Sunday school to mastery Sunday School curriculum subject. In order to improve mastery of Sunday school subject, the use of video media and assignment method must be taken into account. In teaching and learning process, a teacher prepares a number of material to be taught. A teacher has a responsibility to teach material and make sure that the material is absorbed optimally by students who learn by proven through tests. And, How if the students learning by using videos and assignment methods, will it be affected the ability to master the material?